Analisis Kebutuhan Guru dan Peserta Didik Terhadap Pengembangan Bahan Ajar Biologi di SMA - St. Fatmah Hiola; Abd. Muis (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This study aims to analyze the needs of teachers and students for biology teaching materials, especially in Kingdom Plantae material in high school. The method used is a qualitative descriptive method. Data collection was carried out by survey method, with research instruments in the form of teacher and student questionnaires. The data analysis used is by reducing the survey data into more specific data to be presented descriptively. The results showed that teachers and students need the development of teaching materials with more attractive designs and can be used at any time (flexible in their use), so that they can support learning activities anytime and anywhere. Based on this, it was concluded that it is necessary to develop teaching materials in the form of e-books based on mind mapping on Plantae materials so that they can support the learning process in schools.